Representasi Pelecehan Seksual Pada Film Promising Young Woman (Analisis Semiotika Roland Barthes) - A, Jody Kurnia; BP, Ratu Laura Mulia; W, Ratu Nadya (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
The aim off this research is to describe the depiction off sexual harassment in the filmPromising Young Woman by director Emerald Fennell. The research data where analyzed usingRoland Barthes’ semiotic analysis technique which used a two stage signification model, namelydetonatiton, connotation, and myth. The film Promising Young Woman itself tell the story of sexualharassment against woman which ends in revenge. Cassie (Carey Mulligan), a 39 year old womanwho work as a waitress in a coffee shop. Once a medical student, Cassie decide to quit and no longercontinue her education after the tragedy that befell her best friend. In this study the approach usedwas descriptive qualitative with data obtained through observation of film scenes. The result of thisstudy prove that the representation of sexual depiction found in the film Promising Young Womanis evidenced by the presence of signs of sexual harassment values contained in several scenes,whether visualized in pictures or dialogues.